2009
DOI: 10.1063/1.3194798
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanisms of oxygen atoms in the O(D21) state from the 157nm photoirradiation of amorphous water ice at 90K

Abstract: Vacuum ultraviolet photolysis of water ice in the first absorption band was studied at 157 nm. Translational and internal energy distributions of the desorbed species, O͑ 1 D͒ and OH͑v =0,1͒, were directly measured with resonance-enhanced multiphoton ionization method. Two different mechanisms are discussed for desorption of electronically excited O͑ 1 D͒ atoms from the ice surface. One is unimolecular dissociation of H 2 O to H 2 +O͑ 1 D͒ as a primary photoprocess. The other is the surface recombination react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…O͑ 1 D͒ atoms via reaction ͑12͒ were successfully detected following 157 nm photolysis of ASW, 16 but would play only a minor role in the present study, considering the small quantum yields ͑Յ0.01 for 145-185 nm͒ in the gas phase, 10 and high reactivity of O͑ 1 D͒ with parent H 2 O molecules by collisions with ASW to produce OH or H 2 O 2 . 44,45 Our previous study showed that O͑ 3 P͒ atoms were photodesorbed immediately after 157 nm irradiation started, and are mainly formed by recombination of two OH radicals moving on the ASW surface, i.e., reaction ͑13͒,…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…O͑ 1 D͒ atoms via reaction ͑12͒ were successfully detected following 157 nm photolysis of ASW, 16 but would play only a minor role in the present study, considering the small quantum yields ͑Յ0.01 for 145-185 nm͒ in the gas phase, 10 and high reactivity of O͑ 1 D͒ with parent H 2 O molecules by collisions with ASW to produce OH or H 2 O 2 . 44,45 Our previous study showed that O͑ 3 P͒ atoms were photodesorbed immediately after 157 nm irradiation started, and are mainly formed by recombination of two OH radicals moving on the ASW surface, i.e., reaction ͑13͒,…”
Section: Discussionmentioning
confidence: 73%
“…These OH͑v = 0 and 1,T trans = 7500 K͒ can proceed in endothermic reactions on ASW surface. 16 21 pointed out a possibility of the nonadiabatic transition for the OH+ O reaction. The potential energy surface of OH+ O reaction corresponding to the electronically excited 2AЈ state correlates only with the O 2 ͑a 1 ⌬ g ͒ + H product channel through the electronically excited state of the HO 2 ͑2AЈ͒ complex, but nonadiabatic electronic relaxation of this complex to the lowest 2AЉ state can provide O 2 ͑X 3 ⌺ g − ͒ + H product channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the condensed phase with 7.9-eV photons, reaction (4) leads to O( 1 D) desorption with T trans = 800 K. 12 Quenching of these O( 1 D) atoms to the ground state is improbable because O( 1 D) readily reacts with H 2 O to form H 2 O 2 or 2 OH. 28 In the condensed phase, conservation of momentum can involve neighboring water molecules, state mixing can occur due to many-body interactions, and ionization energies can be lowered considerably relative to the gas phase.…”
Section: A O( 3 P J ) Formation By Molecular Eliminationmentioning
confidence: 99%
“…Because photodissociation of water is such an important process in atmospheric, interstellar, and planetary chemistry, it has been studied extensively. [11][12][13][14][15][16] Even when the primary experimental goal is to measure photodesorption of water, a significant amount of photodissociation occurs and complicates the interpretation of measured water removal cross sections. 9,17,18 O( 3 P J ) formation by 157-nm irradiation of 1500 L amorphous solid ASW at 90 K has been measured previously by Hama et al, who found that four Maxwell-Boltzmann components with translational temperatures of 5000, 1300, 300, and 100 K fit their data.…”
Section: Introductionmentioning
confidence: 99%